Pengembangan Visual Branding UMKM di Kelurahan Wonorejo Berbasis Digital Marketing - Roziana Febrianita; Daffa Ammar Mahendra; Fikri Raihan Pratama; Dwi Fibianto (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
MSMEs have a crucial role in the Indonesian economy, but many of them still face obstacles in terms of branding and digital marketing. The lack of understanding of the importance of visual identity and digital strategy causes MSME products to be less prominent in a competitive market. This community service activity aims to improve the quality of branding of MSME products in Wonorejo Village, Pasuruan City, through the Participatory Rural Appraisal (PRA) approach which involves stages of counseling, training, and direct assistance to business actors. The counseling is focused on a basic understanding of visual branding, including elements of brand identity such as logos, colors, typography, and packaging. The training emphasizes hands-on practice in designing promotional packaging, logos, and banners using digital platforms like Canva. Furthermore, mentoring is carried out to identify specific branding obstacles faced by each MSME and develop applicative solutions collaboratively. The results of the activity show a significant increase in the quality of branding MSME products visually and digital marketing strategies. One of the fostered MSMEs, namely AM Jaya and Berkah Mandiri, has succeeded in rebranding packaging and developing digital marketing channels through e-commerce platforms and social media. In addition, business actors become more confident in presenting their products to consumers and business partners. MSMEs are also beginning to realize the importance of brand consistency in building customer loyalty and increasing competitiveness. The response of the participants to this activity was very positive, reflected in the enthusiasm during the training and the commitment to implement the learning outcomes. Some MSMEs are starting to form small communities to share best practices in terms of branding and promotion.